2015
DOI: 10.1002/hed.24349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polo‐like kinase 1 as a potential therapeutic target in Merkel cell carcinoma

Abstract: Because of the marked upregulation of PLK1 in MCC tumor samples and potent inhibition of cell proliferation using a specific clinically available inhibitor, targeting of PLK1 qualifies as a potential novel therapeutic strategy in MCC. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1918-E1925, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In line with our findings, several other studies reported that the combination of Plk1 inhibition with radiotherapy leads to synergistic cell killing in vitro in multiple cancer types such as breast cancer, NSCLC, cervical epithelial adenocarcinoma, medulloblastoma, osteocarcinoma, glioblastoma, Merkel cell carcinoma, colorectal cancer, bladder carcinoma, oral cancer, and esophageal squamous cell carcinoma [8,[28][29][30][31][32][33][34][35][36][37][38][39][40]. In vivo, Dong et al demonstrated a synergistic inhibition of tumor growth and prolonged median survival in a tumor xenograft murine model with glioblastoma stem cells after treatment with volasertib and radiation [38].…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, several other studies reported that the combination of Plk1 inhibition with radiotherapy leads to synergistic cell killing in vitro in multiple cancer types such as breast cancer, NSCLC, cervical epithelial adenocarcinoma, medulloblastoma, osteocarcinoma, glioblastoma, Merkel cell carcinoma, colorectal cancer, bladder carcinoma, oral cancer, and esophageal squamous cell carcinoma [8,[28][29][30][31][32][33][34][35][36][37][38][39][40]. In vivo, Dong et al demonstrated a synergistic inhibition of tumor growth and prolonged median survival in a tumor xenograft murine model with glioblastoma stem cells after treatment with volasertib and radiation [38].…”
Section: Discussionsupporting
confidence: 92%
“…In gastric cancer, BI2536 increased the anti-tumour of DDP in PLK1 overexpressed tumour cell, the Wnt/ β -catenin and MEK/ERK/RSK1 signaling pathways changed under the co-treatment [26]. In several research, the researchers compared the sensitization of various PLK1 inhibitions to radiotherapy and chemotherapy, and found that PLK1 combined with radiotherapy had a better synergistic effect in Medulloblastoma, Merkel cell carcinoma and bladder carcinoma [27,45,46]. Our study is the first to confirm that inhibiting PLK1 could enhance the chemosensitivity of ESCC cells to DDP.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was performed as described elsewhere using the Lab Vision Ultra V Block kit (Thermo Fisher Scientific, Waltham, MA, USA) and the Lab Vision Ultravision LP detection system (Thermo Fisher Scientific, Waltham, MA, USA) according to manufacturers protocol [ 16 ]. Briefly, citrate buffer (pH 6.0) was used for antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%